ANALISIS FAKTOR MINAT SISWA MEMILIH JURUSAN TKJ PADA SMK NEGERI 2 SAMPIT - Sudarmono Sudarmono; Apuanor Apuanor; Novia Dwi Lasenia (STKIP MUHAMMADIYAH SAMPIT, 2018)
This study aims to know the factors that influence the students interest choosing majors a computer and networks in the middle school to vocational country 2 sampit. This study using descriptive quantitative. The population of this research is students secondary school to vocational coutry 2 Sampit majors a computer and network, class X, XI and XII a number of 302 students. The techniques a sample of in this study bstratifrld disproportionately random sempling that amountsnto 75 student, and technique collecting date on the of researchers is the questionnarie or inquiries.Based on the results of the analysis of factor, and the internal factor that influence the students interes choosing in the middle school to vocational country 2 Sampit establishedwith aspects for 0,795, the interests of 0,479, the attention of 0,814 and aspects of interest to indicator angagement of 0,931.internal factor of aspects of interest to indicator involvement affect the students interest choosing majors a computer and the value of 0,931 network.